International perspectives on retention and persistence - Gary Burkholder; Nicole Holland (Laureate Education Inc, 2014)
Access to higher education globally is increasing dramatically; attainment of tertiary degrees is a high priority, as educational attainment is associated with increased personal incomes as well as growth of the middle class in developing countries. The purpose of this essay is to briefly examine retention and persistence issues from a global perspective, review some retention strategies that have been employed at schools outside the United States, and to identify several key factors that related to retention and persistence globally, including access, infrastructure, financial consideration, and readiness for tertiary education.  There exists an opportunity to utilize knowledge gained in the evolution of the higher education system in the United States to help address the problems associated with retention and persistence.   DOI: 10.18870/hlrc.v4i2.208